Diversity of Weeds and Population Dynamics of Predators and Prey Present in Wheat-Mustard Ecosystem at Paklihawa, Rupandehi, Nepal - Khanal, S.; Adhikari, S.; Bhattarai, A.; Shrestha, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study was conducted at Institute of Agriculture and Animal Science (IAAS), Paklihawa Rupandehi, agronomy field to study the diversity of weeds and population dynamics of predators and prey in wheat-mustard ecosystem. The study was conducted by quadrate sampling method using the wooden frame by selecting 40 sample spots, and locating its coordinates. Predator, prey, some of the beneficial and harmful insects as well as weed species was recorded in 5 days interval in the study. Relationships between the population of the mustard aphid and wheat aphid, lady bird beetle to maximum and minimum temperature were recorded in order to know the effect of temperature in relation to population density. Number of mustard aphid and its nymph has shown the positive significant relationship with the population of the spider in the wheat mustard ecosystem. Shannon Weiner Index value was calculated and the species richness was found to be 2.63 with the effective number of species value 9. The species evenness value was found to be 0.83 in the studied ecosystem which signifies that the given weed ecosystem is somewhat even. The importance value index (IVI) of the given ecosystem with the value of different weed species was calculated and it was found that the weed Anagalis arvensis was ranked as first with the IVI value of 57.98 following Vicia sativa and Chenopodium album. This signifies that the species Anagalis arvensis has greater control over the wheat mustard ecosystem of Paklihawa, Rupandehi.